Cross-Cover Chaos to Calm: A Smarter Protocol for Efficient Patient Care - Pinar Ozmen Akkurt; Martin Gracias; Seán Whyte (BJPsych Open)
Aims: To ensure fair workload distribution and faster patient care, SWLSTG follows a cross-cover policy, grouping wards into clusters based on proximity. Each ward has designated cross-cover doctors responsible for daytime medical advice and patient reviews in absence of the ward doctors.